Peningkatan Kualitas Pembelajaran Siswa Tunagrahita dalam Membaca dan Menulis melalui Pendekatan Kooperatif Tipe STAD di Sekolah Luar Biasa - Murtadlo Murtadlo (JPK (Jurnal Pendidikan Khusus), 2006)
The study attempts to improve the achievement of the student with early reading and writing difficulties. The research is designed experimentally. To collect the data, instrumens of test, documentation adn observation are used. The data were analised using non parametric statistic : "The sign test" to student with spesific learnijng difficulties. The result show that student  achievement was increased using cooperative learning type STAD, and according to the result study is it recomendet to develop other learning effective for special student with mentally retarded in special school.